Relevance of religiosity and spirituality in medicine (Research, Society and Development, 2024)
Introduction: Spirituality is related to the feeling of transcendence, elevation, sublimity, religious or mystical activity, while religiosity involves the natural tendency towards religious feelings and sacred things. Both are unique factors for the promotion, prevention and recovery of health. They have an influence on improving quality of life, to the point of reducing the use of health services and contributing to maintaining a healthy lifestyle for the most compromised individuals. Objective: The work intends to evaluate the impact of faith, spirituality and religiosity for individuals in a situation of illness, and how it influences the way of dealing with this scenario. Methodology: This is an integrative literature review carried out between December 2022 and January 2023 in the following databases: National Library of Medicine (PubMed MEDLINE), Scientific Electronic Library Online (Scielo), Google Scholar, Biblioteca Virtual Health (VHL), Web of Science and EBSCO Information Services. Results and discussion: It was clearly explained that religiosity and spirituality go together for a good prognosis for the patient, many individuals express that the professional's support in their beliefs alleviate their suffering and anxieties. Final considerations: Most articles describe the influence of R/S on the improvement of the patient, as a whole, with better coping with the disease, increased well-being, purpose, etc. without any association or definition of prognosis or therapy.